Degree of zootechnics: Barometer of economic development in the world countries - Emilian Merce; Cristian Călin Merce; Iulia Mureşan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The paper presents debates and analyses the causal relation between the level of economic development and the degree of development of the animal husbandry sector. There is a large variability in time and space at the level of the world's countries regarding this aspect. As a general trend it was observed in time an increase of the degree of development of the animal husbandry sector, with high differences among the countries being directly link to the level of development of each country. The sources of information used are the data base of FAOSTAT, world bank and EUROSTAT. There were collected data regarding the GDP per capita and the share of the value of animal husbandry production in the value of agricultural production. The data were analyzed for 14 countries from different geographical area. The main method of research and analysis was the index method. The influence of the economic development on the development of the degree of animal husbandry sector is revealed by using the regression and correlation method. The results prove that modern agriculture cannot exist in a rudimentary economy. The first step to the modernization of the agriculture consists in increasing the degree of development of the animal husbandry sector. at the same time the economic development level of a country is the consequence of development and uniform combination of the all branches of the economy (industry, transports, infrastructure, services etc.) all these determine the social structure of the country.
Keywords: 330; economic development; animal husbandry development; index; regression; correlation